TINJAUAN YURIDIS PERLINDUNGAN HUKUM TERHADAP NOTARIS MELALUI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 84 TAHUN 2024 TENTANG BATAS USIA PENSIUN NOTARIS - Khansa Hurruzia (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The Law Number 2 of 2014 relating to the Office of Notary (UUJN) contains the rights and obligations of the Notaries as public officials who have important authority to make authentic deeds and keep legal documents that have legal evidentiary power. On the other hand, Notaries also have rights including the authority to make authentic deeds, maintain the confidentiality of client data, and obtain legal protection. Legal protection is the most important thing for notaries in carrying out their duties and functions in the community. However, this legal protection is restricted by a fairly short age limit for Notaries in carrying out their role as a public official. In response to this, a judicial review was submitted through the Constitutional Court regarding the age limit issue. This fact raises the issue: why is it necessary to extend the retirement age limit for Notaries in Indonesia and to what extent this age limit can provide legal protection for Notaries. This research is a normative juridical research with qualitative data that emphasizes secondary data through the application of norms, rules in positive law, and statutory approaches. The research results show that: First, the extension of the retirement age limit for Notaries in Indonesia is needed to maximize the function of Notaries so that they have more time to fulfill the necessities of their life and carry out their functions in society; Secondly, the age limit can provide a longer period of statutory legal protection for Notary to perform their duties and functions in the community, improving the livelihood of themselves, their children, wives and families through their role in the Indonesian legal repertoire.